PERAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KULTUR SEKOLAH DI SD MUHAMMADIYAH SANGONAN 2 - Fahmadinna Ilmasari; Said Alhadi (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
ABSTRACT                This study aims to answer: 1) the role of school principals in developing school culture in Muhammadiyah Sangonan Elementary School 2, 2) supporting factors and obstacles for school principals in developing school culture in SD Muhammadiyah Sangonan 2.This type of research uses descriptive qualitative research. The subjects of this study were principals, teachers and students. Data collection techniques using triangulation techniques and sources. Data analysis techniques using interactive data models Miles and Huberman.The results of the study are as follows: 1) the role of the principal in developing school culture through 4 roles namely the role of the principal as manager, the role of the principal as leader, the role of the principal as an innovator and the role of the principal as motivator. The role of the principal as a manager includes the principal taking actions or efforts taken to develop school coursework (compiling the program), joint efforts of the teacher in developing a better school culture, mobilizing teachers to take part in implementing the developed school culture. Keywords: School Culture and the Role of Principals.